2017
DOI: 10.1186/s12935-017-0455-1
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological significance of UBE2C in breast cancer: a study based on immunohistochemistry, microarray and RNA-sequencing data

Abstract: BackgroundUbiquitin-conjugating enzyme E2C (UBE2C) has been previously reported to correlate with the malignant progression of various human cancers, however, the exact molecular function of UBE2C in breast carcinoma (BRCA) remained elusive. We aimed to investigate UBE2C expression in BRCA and its clinical significance.MethodsThe expression of UBE2C in 209 BRCA tissue samples and 53 adjacent normal tissue samples was detected using immunohistochemistry. The clinical role of UBE2C was analyzed. Public databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 50 publications
(39 reference statements)
7
49
0
Order By: Relevance
“…12 and encodes a member of the E2 ubiquitin-conjugating enzyme family, which is required for the destruction of mitotic cyclins and for cell cycle progression [7]. Recent literature has reported that UBE2C plays critical role in the progression of non-small cell lung cancer [8], gastric cancer [9] and breast cancer [10]. Only one article reported that UBE2C expression in endometrial carcinoma group was significantly higher than that in benign and hyperplastic tissues [11].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…12 and encodes a member of the E2 ubiquitin-conjugating enzyme family, which is required for the destruction of mitotic cyclins and for cell cycle progression [7]. Recent literature has reported that UBE2C plays critical role in the progression of non-small cell lung cancer [8], gastric cancer [9] and breast cancer [10]. Only one article reported that UBE2C expression in endometrial carcinoma group was significantly higher than that in benign and hyperplastic tissues [11].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Higher expression of UBE2C draws a parallel with the progression of various human cancers including breast cancer. 12 Western blot analysis conrmed the expression of UBE2C in MCF-7 cell line (Fig. 1C).…”
Section: Real Sample Analysis With the Developed Immunosensormentioning
confidence: 97%
“…11 Particularly, upregulation of UBE2C frequently causes malignant phenotype in breast cancer as observed in previous reports. [12][13][14][15][16] We also analyzed the prognostic value of the UBE2C in breast cancer with BreastMark tool. 17 The survival rate of patients with higher expression of UBE2C was found to be signicantly lower (P ¼ 1.1102 Â 10 À16 ) than those with lower expression of UBE2C ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…UBE2C is a crucial component of the ubiquitin-conjugating enzyme complex, which is involved in the ubiquitin-proteasome system 55 . Studies proved that overexpressed UBE2C was linked to poor prognosis in BC 56 .…”
Section: Analysis Of Core Genes By the Kaplan Meier Plotter And Gepiamentioning
confidence: 99%